Teaching strategies for promoting female college students' physical activity - Ma, Ji; Guo, Yuqiang; Zhu, Chao; Wen, Chunyuan; Deng, Qiaoqiao; Ma, Xiao (Frontiers in Psychology, 2025)
BackgroundAlthough physical activity (PA) levels among female students have improved in primary and secondary education, female undergraduates consistently show lower PA levels compared to males and younger female students. Previous studies suggest that gender stereotypes and socially constructed traits significantly impact females' choices and engagement in sports. This study examines how gender roles and sports type choices influence PA levels and physical exercise involvement among female undergraduates.MethodCluster sampling was used to recruit 500 undergraduates (256 males, 244 females) from five universities in Shanghai. Valid data from 439 undergraduates (mean age = 19.02 ± 1.04 years) were collected using the Physical Activity Rating Scale (PARS-3), Chinese College Students' Sex-Role Inventory (CSRI-50), and Physical Exercise Involvement Scale (PEIS). Data were analyzed through descriptive statistics, chi-square tests, and ANOVA.ResultsFemale undergraduates had significantly lower PA and physical exercise involvement scores compared to male peers (PA: p < 0.001, Cohen's d = 0.494; involvement: p < 0.001, Cohen's d = 0.752). No significant gender differences were observed in sports choices (p = 0.402). Female undergraduates showed the lowest PA levels in masculine sports (p = 0.002). Among female participants, gender roles significantly affected PA and involvement, with androgynous individuals performing best, especially in masculine sports (PA: p < 0.001; involvement: p < 0.001). Feminine and undifferentiated roles were associated with lower scores in value cognition (p < 0.001) and autonomy (p < 0.001).ConclusionGender stereotypes significantly impact female undergraduates' PA levels and physical exercise involvement. Promoting androgynous traits and reducing gender-role constraints in educational contexts can enhance female undergraduates' PA engagement. Future educational strategies should emphasize gender inclusivity and autonomy to address existing gender-related disparities in sports participation.